2011
DOI: 10.1080/00015458.2011.11680774
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Retrieval of Gossypibomas—Short Series and Review of Literature

Abstract: Gossypibomas, among abdominal foreign bodies, represent a certain reality with significant legal implications. Prevention should prevail and all efforts should be made in such respect. Laparoscopic approach is possible in selected cases (small swabs, encapsulated, no complications).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 14 publications
(19 reference statements)
0
26
0
1
Order By: Relevance
“…Only in one patient they converted to open surgery due to intense adhesion of foreign body to the stomach wall. At the end of the study they concluded that laparoscopy can be safely implemented in small, encapsulated sponge without complication [ 16 ]. Justo et al detected the retained item as a gastrointestinal stromal tumour, after 34 years from their first operation due to peptic ulcer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Only in one patient they converted to open surgery due to intense adhesion of foreign body to the stomach wall. At the end of the study they concluded that laparoscopy can be safely implemented in small, encapsulated sponge without complication [ 16 ]. Justo et al detected the retained item as a gastrointestinal stromal tumour, after 34 years from their first operation due to peptic ulcer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure can be done by laparotomy or by laparoscopy. Laparoscopic retrieval of textilomas is indicated in selected cases where there are no complications, where the forgotten swab is small and encapsulated [10]. …”
Section: Discussionmentioning
confidence: 99%
“…cotton) and the swahili word boma (concealed mass) . RSM is a serious medical problem, which, despite its rare reporting, must be handled as potential differential diagnoses for patients presenting after abdominal surgery with nonspecific abdominal issues …”
Section: Introductionmentioning
confidence: 99%
“…6 RSM is a serious medical problem, which, despite its rare reporting, must be handled as potential differential diagnoses for patients presenting after abdominal surgery with nonspecific abdominal issues. 1,[7][8][9] Primary aim of this case report is therefore, even though standardized procedures and checklist should minimize the risk for RSM, to remind surgeons of Gossypiboma as potential reason for patients presenting with surgical complications.…”
Section: Introductionmentioning
confidence: 99%